Paper No P24: Effect of Mechanical Strain on Charge‐Transfer VT‐Shift Compensation Circuits for Flexible AMOLED Displays. Issue 1 (September 2015) - Papadopoulos, Nikolas P.; Lee, Czang‐Ho; Sachdev, Manoj; Wong, William S.
Abstract A 4‐thin‐film transistor (TFT) voltage‐programmed pixel circuit is fabricated using low‐temperature (170°C) hydrogenated amorphous silicon (a‐Si:H) TFTs process on flexible polyethylene naphthalate substrate. The electrical stability of the 4‐TFT circuit was characterized under mechanical strain and flat (unstrained) conditions. The compensated drive current degraded approximately 5% under electrical bias and tensile strain. This result was similar to pixel circuits fabricated at high temperature (300°C) on rigid glass substrates.